2017
DOI: 10.1002/elan.201700669
|View full text |Cite
|
Sign up to set email alerts
|

Ion Transfer Voltammetry at Thin Films Based on Functionalized Cationic [6]Helicenes

Abstract: We describe a new family of molecular ion‐to‐electron redox probes based on cationic diaza, azaoxa, and dioxa [6]helicenes and their derivatives. Their unique structure combines, in a single framework, two privileged families of molecules – helicenes and triaryl methyl carbenium moieties. These cationic [6]helicenes exhibit reversible and reproducible oxidation/reduction behavior and facilitate the ion transfer into thin layer sensing films composed of bis(2‐ethylhexyl)sebacate (DOS), polyurethane (PU), sodium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 28 publications
1
25
1
Order By: Relevance
“…Other applications in electrochemiluminescence or ion transfer voltammetry were also reported for some [4]-and [6]helicene cationic dyes but focused only on racemic compounds. 282,283,284 In collaboration with Prof. Naaman, Lacour investigated aza [4]helicenium derivative [260][BF 4 ] as potential organic spin filter owing to the Chirality Induced Spin Selectivity (CISS) effect. 285,286 Using magnetic conductive probe atomic force microscopy (mCP-AFM) and magnetoresistance measurements set-ups, the authors showed that spin specific electron conduction is measured on chiral helicenium films with an opposite preferred spin for (P) and (M) enantiomers (Figure 38).…”
Section: Applications Of Carbocationic Azahelicenesmentioning
confidence: 99%
“…Other applications in electrochemiluminescence or ion transfer voltammetry were also reported for some [4]-and [6]helicene cationic dyes but focused only on racemic compounds. 282,283,284 In collaboration with Prof. Naaman, Lacour investigated aza [4]helicenium derivative [260][BF 4 ] as potential organic spin filter owing to the Chirality Induced Spin Selectivity (CISS) effect. 285,286 Using magnetic conductive probe atomic force microscopy (mCP-AFM) and magnetoresistance measurements set-ups, the authors showed that spin specific electron conduction is measured on chiral helicenium films with an opposite preferred spin for (P) and (M) enantiomers (Figure 38).…”
Section: Applications Of Carbocationic Azahelicenesmentioning
confidence: 99%
“…They can be dissolved in the membrane phase and mediate the iontransfer across the interface upon their reduction or oxidation. [75][76][77] Jansod et al…”
Section: New and Non-classical Readout Principles For Ion-selective Ementioning
confidence: 99%
“…The ratio between the concentrations of added cation-exchanger and redox probe was found to determine the voltammetric anion or cation response of this system. Cationic diaza, azaoxa, and dioxa [6]helicenes and their derivatives were introduced as another family of molecular redox probes for voltammetric cation 76 and anion 77 is necessary. 77 Unfortunately, it was found that the ionophore based cation- The potentiometric response of nanopores can be understood using the concept of permselectivity in some analogy to conventional polymer membrane ISEs.…”
Section: New and Non-classical Readout Principles For Ion-selective Ementioning
confidence: 99%
See 1 more Smart Citation
“…Another trend in the development of ion‐selective electrodes, also those with a solid contact, is application of dynamic electrochemical methods to interrogate the sensors . Recently, the most popular electrochemical method in this aspect has been voltammetry with thin ion‐selective membranes coated on electrode supports, containing conducting polymer layers or immobilized redox reagents as a transducer . Voltammetric methods are usually used either in a direct mode (recording a voltammetric curve for electrode immersed in the analyte solution, with peak current position determined by the analyte concentration) or in stripping mode, as shown mainly by Amemiya et al.…”
Section: Introductionmentioning
confidence: 99%